2015
DOI: 10.4238/2015.december.16.23
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of microRNA-31 in peripheral blood mononuclear cells for pediatric pulmonary tuberculosis in Chinese patients

Abstract: ABSTRACT. We investigated the diagnostic values of microRNA-31 in peripheral blood mononuclear cells (PBMCs) for pediatric pulmonary tuberculosis in Chinese patients. Sixty-five children with TB were selected for this study, which was conducted at the Department of Infectious Diseases People's Hospital of Laiwu City between December 2013 and December 2014. Sixty healthy children, selected in parallel, served as the control group. Real-time PCR was used to detect miR-31 expression in PBMCs. Serum levels of IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
3
21
0
3
Order By: Relevance
“…Interestingly, an active link between the expression of miRNA and gene expression has been found [30]. Wang et al [97] showed that miR-31 is significantly reduced in patients with TB, compared to the healthy children, and besides, this study indicates that expression of this miRNA has a negative correlation with the levels of IL-6, TNF-α, and IFN. They also argued that the expression profile of miRNAs varies, among many individuals and it is not gendered specific or clinical phenotypedependent, although they were able to distinguish the expression of an active TB group from the latent TB group, using the 17miRNA predicted by the SVM method, most (12 out of 17) upregulated in patients with active TB [7].…”
Section: Other Mirnasmentioning
confidence: 60%
“…Interestingly, an active link between the expression of miRNA and gene expression has been found [30]. Wang et al [97] showed that miR-31 is significantly reduced in patients with TB, compared to the healthy children, and besides, this study indicates that expression of this miRNA has a negative correlation with the levels of IL-6, TNF-α, and IFN. They also argued that the expression profile of miRNAs varies, among many individuals and it is not gendered specific or clinical phenotypedependent, although they were able to distinguish the expression of an active TB group from the latent TB group, using the 17miRNA predicted by the SVM method, most (12 out of 17) upregulated in patients with active TB [7].…”
Section: Other Mirnasmentioning
confidence: 60%
“… Wu et al (2014) uncovered several miRNA-gene interactions differentiating among active TB, LTBI and healthy subjects. Wang et al (2015) discovered that expression of miRNA-31 in pediatric TB patients was significantly lower compared with that in normal children. Furthermore, miRNA-31 expression was negatively correlated with serum levels of IL-6, TNF-α, NF-κ0, and IFN-overed several m- analysis study reported that the current data do not support any association between miR-146a/499 polymorphisms and genetic susceptibility of humans to TB ( Lu et al, 2016 ).…”
Section: Mirnas As Potential Tb Biomarkersmentioning
confidence: 99%
“…During M. bovis infection, miR‐31 turns off transcription of SHH and its own gene by inhibiting MyD88‐medated activation of TNFA expression and SHH signaling (Ghorpade et al, ). Of note, M. bovis is a known causative agent of tuberculosis, and miR‐31 is down‐regulated in patients with tuberculosis (Wang et al, ; Zhou et al, ), suggesting an aberrant immune response that failed to activate miR‐31 .…”
Section: Regulation Of Mir‐31 Expressionmentioning
confidence: 99%